2019
DOI: 10.1111/1541-4337.12423
|View full text |Cite
|
Sign up to set email alerts
|

Chia Seed (Salvia hispanica L.) as a Source of Proteins and Bioactive Peptides with Health Benefits: A Review

Abstract: The consumption of chia seed (Salvia hispanica L.) has increased in recent years due its high content of omega‐3 fatty acids and dietary fiber. This seed also has a high concentration of proteins and essential amino acids, becoming a promising source of bioactive peptides. The objective of this review was to identify the composition and the beneficial effects of chia seeds (S. hispanica L.), their proteins, peptides, and their potential impact on human health. The UniProt database was used to identify the chia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
147
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 186 publications
(156 citation statements)
references
References 99 publications
(173 reference statements)
5
147
0
4
Order By: Relevance
“…[53] Finally, peptides with hydrophobicity ࣘ20 kcal mol −1 are more effective for penetrating the cell membrane and to exercise effects on the molecule. [54] Interestingly, most of the peptides found in DTP and digested protein fractions from chia seed showed these characteristics, [14,32] which may explain the benefits found in the present study.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…[53] Finally, peptides with hydrophobicity ࣘ20 kcal mol −1 are more effective for penetrating the cell membrane and to exercise effects on the molecule. [54] Interestingly, most of the peptides found in DTP and digested protein fractions from chia seed showed these characteristics, [14,32] which may explain the benefits found in the present study.…”
Section: Discussionmentioning
confidence: 57%
“…[31] Therefore, once protein fractions from chia seed were isolated each one had a specific amino acid composition that, after gastrointestinal digestion, generated a variety of peptides with different amino acid composition and sequences; this leads to specific physicochemical properties and different biological effects in the organism. [14,32] Thus, because of this, each digested protein tested in this study showed distinct effects on the inflammation and atherosclerosis processes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations